The Evaluation of Sports Coaching of Water Skiing in Central Celebes - Daipaha, Moh Tris Maulana; Hartono, Mugiyo; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2022)
Development of water skiing in Central Celebes has not run optimally. The purpose of this study is several indicators, including training programs, coaches/athletes, organizational management, infrastructures, and funding. Method used research qualitative evaluation with Stufflebeam's model that consist of context, input, process and product. Data sources: coaches (1 person), athletes (4 people), club administrators (2 person) and KONI Central Celebes administrators (1 person). Data collection techniques using observation, interviews and documentation. Data analysis process was data collecting, reduction, presentation, verification and conclusion. Results: Context, the availability of training program available, incompetent; sufficient coach/athlete, not competent; no sports administrator; adequate infrastructure, not of national standard; government support (funds availability) does not exist. Input, planning of unplanned training program; coach recruitment; unlicensed, athlete; not selection; sports management coordination is not established; unplanned infrastructure; no funds. Process, the implementation of training program is guided, there are obstacles; increase in human resources is not realized; the use of infrastructures is sought; (the use implementation of funds) does not exist. Product, the success of training program has not been maximized; HR performance is not optimal; infrastructures are utilized; inappropriate funds. Conclusion: context, training programs, coaches/athletes and infrastructures are moderate; sports management and government support related to funds availability are lacking. Input, training programs and infrastructures are moderate; coaches/athletes, sports administrators and funds are moderate. Process, infrastructures are good; training program is moderate; coaches/athletes, sports management and funds are lacking. Products, infrastructures are good; training program and coaches/athletes are moderate; sports management and funds are lacking.